Genotyping of GATA4 gene variant (G296S) in Malaysian congenital heart disease subjects by real-time PCR high resolution melting analysis - Fawzi, Nora; Vasudevan, Ramachandran; Ismail, Patimah; Alwi, Mazeni; Abdul Aziz, Ahmad Fazli; Almeamar, Hussein; Mohamad, Nur Afiqa; Etemad, Ali (De Gruyter Open, 2013)
Background: Congenital heart disease (CHD) is the most common birth defect; however, the underlying etiology is unrecognized in the majority of cases. GATA-binding protein 4 (GATA4), a cardiac transcription factor gene, has a crucial role in the cardiogenesis process; hence, a number of heterozygote sequence variations were identified as a cause of CHD. G296S heterozygote variant is the most frequently reported GATA4 gene sequence alteration. This study aims to investigate the role of G296S variant of the GATA4 gene in Malaysian CHD subjects.